A Fantastic Pool of Potentially Huge Funds Behind Tapera - Kumara Adji Kusuma (Indonesian Journal of Law and Economics Review, 2024)
This research examines the controversial Tapera program introduced by the Indonesian government to provide a long-term, low-cost housing fund, analyzing its financial implications and public perceptions. Using secondary data sources and qualitative analysis techniques, this study estimates that the program could generate around IDR 201 trillion per year from Indonesian labor income. However, public sentiment remains mixed, with concerns regarding the mandatory nature of the program and its impact on low-income communities. These findings underscore the need for further exploration of Tapera's alignment with national development goals and its role in addressing housing affordability challenges. Highlights : The Tapera program could generate significant funds annually from Indonesian labor income. Public sentiment toward Tapera remains mixed due to concerns about its mandatory nature and impact on low-income communities. Further exploration is needed to assess Tapera's alignment with national development goals and its effectiveness in addressing housing affordability challenges. Keywords: Tapera program, Indonesian government, housing affordability, public perception, financial implications